SELF PERCEPTION OF ACADEMIC COURSE OF PHYSICAL EDUCATION AND ITS INFLUENCE ON CAREER CHOICE (Fiep Bulletin - online, 2014)
The choice of profession is one of the biggest challenges faced in life, because of the importance which it contains and the difficulties they faced . Moreover , it is not always prepared to make that decision . A good career choice is valuable both for the individual and the community in which it is inserted , it is through the profession that plays a social function . In this context , some groups seem to have quirks , image and body satisfaction , as is the case of academic physical education . The present study aimed to analyze the self-perception of academic physical education and its influence on career choice in a State University of Paraná . Data were collected through a questionnaire and anthropometric measurements . The results showed that most academics are dissatisfied with your body , a phenomenon that is not restricted to females . It can be noticed that the choice of physical education as a profession , predominantly , is not linked to situations of escape , and the absolute majority of individuals who choose this career , because it really makes you want to work in this area . In contrast, those who enter the Physical Education course have no knowledge of what the profession really is and what its importance in society , thus making the choice without information. We conclude that the body , health and body aesthetics are emerging demands of society that deserve special attention in the training of Physical Education .
Keywords: Physical education; self-image; career choice